IDENTIFIKASI DAN MITIGASI KERENTANAN KEKERINGAN DAS MOYO (Identification and mitigation of drought vulnerability in Moyo Watershed) - Endang Savitri; Irfan Budi Pramono (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2018)
ABSTRACTDrought identification is needed as a baseline for its mitigation. Several drought identification methods are available, but they need to be tested in dry climates. The purpose of this study was to identify dry area and its mitigation in Moyo Watershed, West Nusa Tenggara Province. Paimin and Syarif methods were used in the study. The results showed that the Paimin method produced a uniform vulnerability map, which was